A2A Receptor Contributes to Tumor Progression in P2X7 Null Mice - De Marchi, Elena; Pegoraro, Anna; Turiello, Roberta; Di Virgilio, Francesco; Morello, Silvana; Adinolfi, Elena (Frontiers in Cell and Developmental Biology, 2022)
ATP and adenosine are key constituents of the tumor niche where they exert opposite and complementary roles. ATP can be released in response to cell damage or actively released by tumor cells and subsequently degraded into adenosine, which accumulates within the tumor microenvironment. Notably, while ATP promotes immune eradicating responses mainly via the P2X7 receptor (P2X7R), extracellular adenosine acts as a potent immune suppressor and facilitates neovascularization thanks to the A2A receptor (A2AR). To date, studies exploring the interplay between P2X7R and A2AR in the tumor microenvironment are as yet missing. Here, we show that, in C57/bl6 P2X7 null mice inoculated with B16-F10 melanoma cells, several pro-inflammatory cytokines, including interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), interleukin 12 (IL-12), interleukin 17 (IL-17), interferon gamma (IFN-γ) were significantly decreased, while the immune suppressant transforming growth factor beta (TGF-β) was almost three-fold increased. Interestingly, tumors growing in P2X7-null mice upregulated tumor-associated and splenic A2AR, suggesting that immunosuppression linked to lack of the P2X7R might depend upon A2AR overexpression. Immunohistochemical analysis showed that tumor cells’ A2AR expression was increased, especially around necrotic areas, and that vascular endothelial growth factor (VEGF) and the endothelial marker CD31 were upregulated. A2AR antagonist SCH58261 treatment reduced tumor growth similarly in the P2X7 wild type or null mice strain. However, SCH58261 reduced VEGF only in the P2X7 knock out mice, thus supporting the hypothesis of an A2AR-mediated increase in vascularization observed in the P2X7-null host. SCH58261 administration also significantly reduced intratumor TGF-β levels, thus supporting a key immune suppressive role of A2AR in our model. Altogether, these results indicate that in the absence of host P2X7R, the A2AR favors tumor growth via immune suppression and neovascularization. This study shows a novel direct correlation between P2X7R and A2AR in oncogenesis and paves the way for new combined therapies promoting anti-cancer immune responses and reducing tumor vascularization.